Rutas cicloturisticas y su incidencia en el turismo del cantón La Maná, provincia de Cotopaxi. - Sopalo Criollo, Evelyn Johana (2020)
La Maná is one of the seven cantons with greater tourist potential due to its geographical location, climate, inhabitants and its natural and cultural sites. However, this area presents limitations when it comes to adventure tourism such as cycling due to the lack of knowledge, expertise and experience in the tourist field of the inhabitants of the city. With this precedent, the purpose of the present research is to design bicycle tourism routes. Therefore, the research work shows the different activities that can be carried out through cycling. Through the collection of primary and secondary information, the structuring of routes and marketing strategies were carried out. The situational diagnosis of the canton showed the tourist potential of the area as: relevant natural and cultural attractions. Once the results were established, the cycle tourism routes were structured for each of the activities identified along the route. The established packages have a duration of one full day and the design of the routes proposes the implementation of tourist signs. Finally, marketing strategies were established, taking into account the profile of the tourist. A triptych, a logo, a Facebook page and a key ring were designed to inform tourists about the cycling routes.